Transitions and choices : Graduate student mentoring for psychology honours students. - Khoo, Shaun Yon-Seng; Zhao, Jenna; Walker, Adrian; Kirkman, Jessica; Spehar, Branka (Student Success v.10 n.1 p.147-154 https://doi.org/10.5204/ssj.v10i1.648, 2019)
Peer mentoring programs are typically designed to support students transitioning into university. However, recent work has highlighted the importance of supporting transitions through and out of university. The Australian psychology honours year is a particularly stressful period that involves transitioning through university into the research environment and is soon followed by transitions into the workforce or postgraduate study. The School of Psychology at the University of New South Wales, Australia (UNSW) recently developed a graduate/honours peer mentoring program. Pairs of PhD students mentor small groups of honours students in monthly meetings, discussing various aspects of honours and career options. Most honours students sign up for mentoring and evaluation results show that mentees find the program helpful, most frequently acknowledging that their mentors helped them with general advice and understanding their career options. Peer mentoring can therefore support psychology student transitions through and out of university. [Author abstract]